Implementation of space vector modulation for two level three-phase inverter using dSPACE DS1104 - Ismail Bouyakoub; Rachid Taleb; Hacene Mellah; Abdelaziz Zerglaine (Institute of Advanced Engineering and Science, 2020)
With increasing research and advancement in solid-state power electronic devices and microprocessors, various inverter control techniques employing pulse width modulation (PWM) are becoming popular especially in AC motor drive applications. The most commonly used techniques are sinusoidal PWM (SPWM) and space vector modulation PWM (SVPWM). SVPWM is considered to be superior to the SPWM because of better DC bus utilization. In this paper, a real-time digital implementation of SVPWM algorithm for three-phase two level inverter using dSPACE DS1104. The results obtained from the experimentation are closer to that of simulation, which confirms the validity of the implemented algorithm.